After the Rite : Stravinsky's path to neoclassicism (1914-1925) - Carr, Maureen A. (Oxford University Press, 2014)
This title traces the evolution of Stravinsky's compositional style as he searched for his own voice in the explosive musical world of the early 20th century as he responded to harsh criticisms of his work.